Do In Shiatsu Massage dan Latihan Keseimbangan dalam Menurunkan Risiko Jatuh pada Lansia - Bettywati E. Tumanggor; Yellyanda Yellyanda; Debbie Nomiko; Mohd. Syukri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the effect of shiatsu massage and balance exercises in reducing the risk of falling in older people. This quasi-experimental study used a Pretest-Posttest Control Group design. The results showed that the condition of the do in the shiatsu massage group before the intervention had a high risk of 8 (47.05%), then decreased to 2 (29.41%) after the intervention. The pre-test conditions in the balancing exercise group showed a high risk of 5 (29.41%) and decreased to 1 (5.88%) after the intervention. This indicates that both interventions reduce the risk of falling in older people. Statistically, using the Paired t-test showed that the two interventions significantly reduced the risk of losing in the elderly p-value <0.05. In conclusion, the intervention of do in shiatsu massage and balance training reduces the risk of falling in older people. Keywords: Do In Shiatsu Massage, Elderly, Balance Exercise, Fall Risk